Uttar Pradesh Five Year Plan A Progress Review September, 1953 - Planning Commission (Planning Commission, 1953)
Remarks about Cane Development Schemes only:— Target for the your 1050-51, 1951-55 and 1955-56 have been fixed from out of the remainder of total target for the 1 year 1951-56 after subtracting the work already accomplished dining the years 1951-52 and 1952-53. This was done in only- to get the full target completed within the prescribed time. originally there was a slim ne under the Five-Year Finn to sink Tube-wells has now been taken up by the State Irrigation Department. Some Co-operative Tube-wells ate also being sunk and the Can zones and their soviet as an taking full advantage of this scheme. There was no proper method in vogue for assessing the average yield of Sugarcane during 1951-52. A crop cutting Mercy was conducted on plant cane on whose basis the overall average yield was estimated at mounds per acre. On the basis of Crop Cutting survey vonaum during 952-53 in the zones both on Hunt and Batoon.
Government of Uttar Pradesh